"Parlando" in the written language of science? - Olszewska, Danuta (Papers in Linguistics, 2019)
The article explores specific structures organizing written scientific texts within which there is a clear rivalry between formal and informal style. The result of this competition is the hybridization of text genres and the phenomenon of so-called ‘parlando’ which has been adopted from the field of musicology and means writing similar to speaking. To illustrate the ‘parlando’ phenomenon, a doctoral dissertation is used, as it represents a typical text genre in the field of scientific research. The question at issue was how young authors approach nowadays one of the essential features of scientific style, namely objectivity. To investigate this, German and Polish texts from the field of the humanities, texts in which similar stylistic tendencies occur on the metacommunicational level, were taken into account. The main purpose of this study is to identify the characteristics of the ‘parlando’ phenomenon, to indicate its causes and to determine its effects on the stylistic form of contemporary scientific texts.